1995
DOI: 10.1016/0895-7061(95)00231-d
|View full text |Cite
|
Sign up to set email alerts
|

An in-depth examination of the excretion of albumin and other sensitive markers of renal damage in mild hypertension*

Abstract: In an in-depth examination to better define the renal effects of mild hypertension, we used urinary proteins to indicate damage to the glomerulus (albumin), tubular reabsorption capability (retinol-binding protein), and turnover of tubular tissue (alanine aminopeptidase and N-acetyl-beta-D-glucosaminidase) in a group of 18 people with mild hypertension not associated with diabetes and a control group (n = 12). The participants' activity was controlled on a high normal salt diet for 3 days followed by a low sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…27 and 48) and retinol binding protein 4 (Rbp4; see Ref. 29) and increased expression of ␤ 2 -glycoprotein I (apolipoprotein H; see Refs. 13 and 44).…”
Section: Discussionmentioning
confidence: 99%
“…27 and 48) and retinol binding protein 4 (Rbp4; see Ref. 29) and increased expression of ␤ 2 -glycoprotein I (apolipoprotein H; see Refs. 13 and 44).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, microalbuminuria has been linked to risk of having cardiovascular disease, renal failure, stroke, and high blood pressure (Mueller et al 1995;Murtaugh et al 2003;Lane 2004), but Cd exposures of subjects were not considered in these studies. A potential link between hypertension and mild renal dysfunction was suggested by an observation that subjects with mild hypertension who had microalbuminuria also excreted elevated N-acetyl-β -D-glucosaminidase (NAG) in the urine (Mueller et al 1995).…”
Section: Renal CD Toxicities and Adverse Health Outcomesmentioning
confidence: 99%
“…Since urinary excretion of RBP had been previously validated as a sensitive and accurate marker of early renal tubular injury, it is suggested that a combination of tubular and glomerular malfunction may be responsible for some cases of mixed proteinuria (21).…”
Section: Discussionmentioning
confidence: 99%